Determination of Optimum Carbon Content of LiFePO4 Cathode Material for Lithium Ion Batteries - GOKTEPE, HUSEYIN; SAHAN, HALIL; PATAT, SABAN (Asian Journal of Chemistry, 2010)
In order to optimize carbon content on LiFePO4/C, six samples were synthesized. The samples of LiFePO4/C were synthesized with the addition of 12.5, 25, 40, 50, 70 and 100 % wt. of white sugar as carbon precursor. The amount of carbon in synthesized samples were found to be 2, 4.5, 7, 10, 12 and 17 % wt., respectively. It is found that in this synthesis condition, ca. 17 % of the white sugar converted to carbon. All samples were characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), differancial thermal analysis/ thermal gravimetry DTA/TG and electrochemical properties of composite cathodes were investigated. The particle size of the powders which calcined at 700 °C for 10 h is about 1-2 μm. The electrochemical results showed that, the LiFePO4/C (carbon content was 10 % wt.) cathode material delivers the first discharge capacity of 154 mAh g-1, i.e. 91 % of the theoretical capacity (0.1 C-rate) between 2.5 and 4.5 V (vs. Li/Li+).